Enhancing Students’ Achievement In Writing Text Using Group Investigation Method - Jenny Ika Misela; Mahendra Puji Permana Aji; Khoiriyah Khoiriyah (Jompa Research and Development, 2026)
Group Investigation (GI) is an organizational approach that allows a class to work actively and collaboratively in small groups and enables students to take an active role in determining their own learning goals and processes. This study is aimed at investigating the implementation of GI to enhance the students’ writing ability. This study was conducted by using classroom action research that has two cycles within. The subject of the research was first grade students of English Department UNP Kediri. The instruments of collecting data were quantitative (writing test) and qualitative data (observation sheet, and field notes). Based on the writing test scores, the students’ score kept improving in every test. In the pre-liminary study, there were only 43% of the students who passed the minimum standard score. After giving treatment to the students using GI, 91% of the students passed the test in cycle 1 and 100% of the students passed the test in cycle 2. The students can be more active in group work, and they can follow the process of writing well-ordered by implementing the steps of GI. The result of the research showed that GI method could enhance students’ achievement in writing instruction text.